Keputusan Petani dalam Memilih Mengelola Sagu (Metroxylon Sago Rottb) dan Faktor-Faktor yang Mempengaruhi di Kecamatan Malangke Barat, Kabupaten Luwu Utara - Arin Saputri; Nurdin Lanuhu; Saadah Saadah; Rahmawaty Nadja; A. Amrullah (Hasanuddin University, 2021)
The purpose of this study is 1) measuring the level of decision of sago farmers in terms of external factors 2) analyze the relationship between external factors and internal factors of sago farmers. The research data was collected from 60 respondents with a questionnaire filling method and analyzed through descriptive statistical analysis, frequency tabulation and spearman rank correlation. The study was conducted in March to April 2019 in West Malangke District. The results showed that the preference level of managing sago in Malangke Barat District was high with an average value of 30.85. Economic factors obtained from planting sago dominate the reasons for people's interest in managing sago, followed by food needs and ecological factors. Socio-economic characteristics of respondents such as education level, age, number of family dependents, farming experience, sago land area and income, has a non-significant correlation in the level of preference, because the correlation value obtained is low. Keywords : sago; preference level; socio-economic characteristics.